Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am looking at the following lambda calculus expression: (λx.(λy.(x(λx.xy))))y. Could somebody help me to evaluate it? I am guessing that the first step would be to pass the outermost y into the outer most function λx, but I am unsure where to go from there.

share|cite|improve this question
up vote 1 down vote accepted

First we have to rename the bound $y$ to $z$ to avoid capture: $$(\lambda x.(\lambda z. (x(\lambda x.xz))))y$$ Then we may substitute $y$ for any bound occurence of $x$: $$(\lambda z. (y(\lambda x.xz)))$$

share|cite|improve this answer
Thanks. The process would be the same whether we do it in normal or applicative order, right? – John Roberts Apr 17 '13 at 0:25
Yes, that shouldn't matter. – Abel Apr 17 '13 at 0:26
Could you check this one out too?… – John Roberts Apr 17 '13 at 0:39

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.